USP7: Novel Drug Target in Cancer Therapy - Zhiru Wang; Zhiru Wang; Zhiru Wang; Wenting Kang; Wenting Kang; Yinghua You; Yinghua You; Jingru Pang; Jingru Pang; Hongmei Ren; Hongmei Ren; Zhenhe Suo; et al. (Frontiers Media S.A., 2019)
Ubiquitin specific protease 7 (USP7) is one of the deubiquitinating enzymes (DUB) that erases ubiquitin and protects substrate protein from degradation. Full activity of USP7 requires the C-terminal Ub-like domains fold back onto the catalytic domain, allowing the remodeling of the active site to a catalytically competent state by the C-terminal peptide. Until now, numerous proteins have been identified as substrates of USP7, which play a key role in cell cycle, DNA repair, chromatin remodeling, and epigenetic regulation. Aberrant activation or overexpression of USP7 may promote oncogenesis and viral disease, making it a target for therapeutic intervention. Currently, several synthetic small molecules have been identified as inhibitors of USP7, and applied in the treatment of diverse diseases. Hence, USP7 may be a promising therapeutic target for the treatment of cancer.